A7 OPPORTUNISTIC PATHOGEN MODULATION OF GLUTEN-REACTIVE CD4+ T CELL ACTIVATION BY DQ2-EXPRESSING ORGANOID MONOLAYERS. (7th March 2023) - Rahmani, S; Caminero, A; Hann, A; Galipeau, H J; Anderson, R P; Chirdo, F; Didar, T F; Verdu, E F
Abstract: Background: Bacteria have recently emerged as additional modulators of inflammation in CeD. We have shown that the elastase-like producing opportunistic pathogen, Pseudomonas (P) aeruginos a, partially metabolizes gluten into peptides that translocate the mucosal barrier and retain their immunogenicity. We previously demonstrated that organoid monolayers derived from DR3-DQ2 mice carrying the CeD risk gene HLA-DQ2 express MHC class II (HLA-DQ2) and co-stimulatory molecules under induced inflammatory conditions, priming the monolayers for gluten antigen presentation. Here we investigate the activation of human (h)CD4 + T cell co-cultured with DQ2 monolayers stimulated with gluten pre-digested, or not, by bacterial elastase. Purpose: To investigate whether organoid monolayers expressing DQ2 activate T cell differentially in the presence of gluten metabolized by elastase-like producing Pseudomonas aeruginosa. Method: Organoid monolayers were derived from the duodenum and proximal jejunum of gluten-sensitized DR3-DQ2 mice, following the gluten sensitization protocol previously described 1 . Monolayers were then stimulated with IFN-γ for 24h to induce MHC-II and co-stimulatory molecules expression. Splenic T-cell expressing hCD4 from gluten-sensitized DR3-DQ2-hCD4 mice were then co-cultured with monolayers in the presence of deamidated pepsin-trypsin-digested (DAPT)-gluten or Pseudomonas aeruginosa PA14 (WT)-digested DAPT-gluten. As a control, DAPT-gluten was incubated with a P. aeruginos a las B mutant strain that lacks elastase-like activity ( las B △/△ ). Co-cultures stimulated with DAPT-gluten alone or WT-media were used as additional controls. Result(s): Increased hCD4 + T-cell proliferation was observed in co-cultures stimulated with WT-digested gluten compared with las B △/△ -digested gluten ( p<0.0001 ), gluten alone ( p=0.0002 ) or WT-media ( p<0.0001 ). hCD4 + T cell co-cultured with organoid monolayers stimulated with WT-digested gluten, had an activated phenotype with increased expression of CD69, CD44 and CD25 versus those stimulated with gluten, las B △/△ -digested gluten, or WT-media. Increased levels of pro-inflammatory and T helper type 1 (Th1)-associated cytokines were detected in the supernatant of the co-cultures stimulated with WT-digested gluten, including IL-2, IFN-γ, IL-6, TNF-α, IL-1α, IL-β, and IL-15. Conclusion(s): Using a novel HLA-DQ2-expressing organoid monolayer, we demonstrate elastase-like producing P. aeruginosa, enhanced activation and proliferation of hCD4 + T cell through gluten metabolism. This in vitro model constitutes a relevant tool for studying microbial triggers and drivers of intestinal epithelial dysfunction in CeD. 1. Galipeau, H. J. et al. 1. Galipeau, H. J. et al. Sensitization to Gliadin Induces Moderate Enteropathy and Insulitis in Nonobese Diabetic-DQ8 Mice. J. Immunol. 187, 4338–4346 (2011). Please acknowledge all funding agencies by checking the applicable boxes below: CIHR, Other Please indicate your source of funding: Canadian Celiac Disease Association (CCA) Disclosure of Interest: None Declared